The class compromised? Satawu and organised labour’s ‘The reconstruction of Spoornet’ Initiative - McGregor, Warren (My University, 2018)
This research project evaluates the radical reform strategy of the Congress of South Africa Trade Unions (Cosatu). It locates its theoretical departure point as the debates between those commentators and activists for and against radical reform both within and outside of the trade union movement. [No abstract provided. Information taken from introduction].
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts (Sociology) 2018